Фактори впливу на формування рільничої культури підльвівських сіл (20 – 30-ті рр. ХХ століття) - Захарчин, Наталія Геннадіївна; Zakharchyn, Natalia G. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Розглянуто питання підвищення рільничої культури підльвівських сіл у міжвоєнний період (1918 – 1939 рр.). Окреслено головні напрями впливу на сільськогосподарську культуру Львівського повіту з боку як державних установ Другої Речі Посполитої, так і різноманітних чинників недержавного характеру.The issue of increase of tillage culture in near-Lviv villages in interwar period (1918-1939) is considered. The main vectors of influence on agriculture in Lviv county undertaken by both state bodies of Second Polish Republic and various factors of non-governmental nature. The tillage culture in near-Lviv villages was on the stage of development and reformation. The peculiarity of its formation was the activity (conducted within the villages) of number of various cultural and educational organizations of the region. It is noted that the great influence on development of agriculture not only in Lviv powiat but generally in whole Rzeczpospolita was enjoyed by Ukrainian public organizations. It is determined, that tillage culture in villages in Western Ukraine, including near-Lviv villages carried out the function of realization of peasants' interests, assuring the efficiency of agriculture in the period of economic crysis of the state and the worldwide crysis.
Factors of influence on formation of tillage culture of near-Lviv villages (1920th-1930th)
Keywords: культура сільського господарства; рільнича культура; Львівське воєводство складі в Другої Речі Посполитої; agriculture; tillage culture; Lviv voivodeship under Second Polish Republic